2016
DOI: 10.1177/1357633x15621848
|View full text |Cite
|
Sign up to set email alerts
|

A New mHealth application to support treatment of sleep apnoea patients

Abstract: Introduction Continuous positive airway pressure (CPAP) is the first-choice treatment for obstructive sleep apnoea (OSA), but adherence is frequently suboptimal. Innovative, patient-centred interventions are, therefore, needed to enhance compliance. Due to its low cost and ubiquity, mobile health (mHealth) technology seems particularly suited for this purpose. We endeavoured to develop an mHealth application called "APPnea," aimed at promoting patient self-monitoring of CPAP treatment. We then assessed the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Individualised health tracking through the use of Webbased and smartphone apps is likely to play a more prominent role in delivering future CPAP interventions and in providing behavioural feedback and measuring effectiveness, with online CBT shown to be effective in the treatment of insomnia [86]. Recently, severe OSA patients who regularly used a mobile health technology app BAPPnea^aimed at promoting self-monitoring of treatment had higher CPAP adherence [87]. Studies addressing the choice of interventions that best match individual patient needs/characteristics are likely to be more effective and cost efficient.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…Individualised health tracking through the use of Webbased and smartphone apps is likely to play a more prominent role in delivering future CPAP interventions and in providing behavioural feedback and measuring effectiveness, with online CBT shown to be effective in the treatment of insomnia [86]. Recently, severe OSA patients who regularly used a mobile health technology app BAPPnea^aimed at promoting self-monitoring of treatment had higher CPAP adherence [87]. Studies addressing the choice of interventions that best match individual patient needs/characteristics are likely to be more effective and cost efficient.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…Several clinical trials have demonstrated the feasibility of telemedicine-based OSA management compared with a more traditional, in-person care model, suggesting noninferiority in terms of adherence to CPAP treatment [7], CPAP compliance [8] as well as functional outcomes such as satisfaction [9] and cost-effectiveness [10,11]. In our previous experience using telemedicine for OSA management, we found positive feedback with videoconference and mobile health (mHealth) interventions [12,13]. We also conducted a telemedicine-based strategy for CPAP follow-up which was as effective as standard hospital-based care in terms of CPAP compliance and symptoms improvement, as well as lower costs [11].…”
Section: Introductionmentioning
confidence: 92%
“…SleepMapper also helped those patients who struggled early with therapy compared with patients who did not use the app. In keeping with these findings, Isetta et al 8 designed, developed, and tested a novel App called AppNea, which aimed to promote self-monitoring of CPAP therapy in patients with OSA. They included 34 patients with diagnosed OSA, and asked them to use AppNea for 6 weeks while receiving CPAP treatment.…”
Section: Appsmentioning
confidence: 99%
“…7 Therefore, a major challenge for sleep specialists is optimizing patient compliance, especially when initiating treatment, yet overloaded sleep units have trouble providing such support because of a lack of financial resources. 8 TH has the potential to deliver effective and convenient care that can improve compliance and patient satisfaction, and reduce absenteeism to attend specialist sleep centers. 9 We thus performed a systematic review of the published literature on the role of telemedicine compared to routine face-to-face care for monitoring and improving outcomes in patients with OSA receiving CPAP therapy, with special consideration to phone calls, videoconferencing, e-mails, websites, mobile texting, and mobile applications.…”
Section: Introductionmentioning
confidence: 99%